2023
DOI: 10.3390/ijms24087001
|View full text |Cite
|
Sign up to set email alerts
|

RUNX2 and Cancer

Abstract: Runt-related transcription factor 2 (RUNX2) is critical for the modulation of chondrocyte osteoblast differentiation and hypertrophy. Recently discovered RUNX2 somatic mutations, expressional signatures of RUNX2 in normal tissues and tumors, and the prognostic and clinical significance of RUNX2 in many types of cancer have attracted attention and led RUNX2 to be considered a biomarker for cancer. Many discoveries have illustrated the indirect and direct biological functions of RUNX2 in orchestrating cancer ste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 75 publications
(110 reference statements)
0
11
0
Order By: Relevance
“…This also applies to extraskeletal osteosarcomas which frequently originate primarily from soft tissues, especially those of the mammary gland and manifest as poorly differentiated sarcomats, which are difficult to classify due to the absence of characterizing morphological features such as osteoid. Recent studies, such as that of Lin ( 10 ), also report on the critical role of RUNX2 in the dynamics of progression in different tumor types ( 16 ). It has been reported that RUNX2 may participate in the modulation of several key processes in cancer progression, including transdifferentiation and cancer stem cell potential, angiogenesis, proliferation and metastasis mechanisms, and potential drug resistance ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…This also applies to extraskeletal osteosarcomas which frequently originate primarily from soft tissues, especially those of the mammary gland and manifest as poorly differentiated sarcomats, which are difficult to classify due to the absence of characterizing morphological features such as osteoid. Recent studies, such as that of Lin ( 10 ), also report on the critical role of RUNX2 in the dynamics of progression in different tumor types ( 16 ). It has been reported that RUNX2 may participate in the modulation of several key processes in cancer progression, including transdifferentiation and cancer stem cell potential, angiogenesis, proliferation and metastasis mechanisms, and potential drug resistance ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
“… RUNX2′s modulations to hallmarks of cancer [modified from Lin ( 10 )] and dysregulation of KPNA2 (overexpression) in promoting cancer cells [modified from Han and Wang ( 17 )]. …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Runtrelated transcription factor 2 (RUNX2) is a well-known master regulator of osteoblast and chondrocyte differentiation, Latest findings suggest it promotes cancer progression by regulating cell proliferation, migration, and drug resistance. 124 Chen et al 47 found that HCG18 can upregulate the expression of RUNX2 by sponging miR-34a, thereby promoting the proliferation, migration and invasion of OS cells.…”
Section: Osteosarcoma (Os)mentioning
confidence: 99%